Asymmetric monetary policy spillovers: The role of supply chains, credit networks and fear of floating - Jakub Mistak; F. Gulcin Ozkan (European Central Bank (ECB), 2024)
This paper examines the asymmetry in global spillovers from Fed policy across tightening versus easing episodes several examples of which have been on display since the global financial crisis (GFC). We build a dynamic general equilibrium model featuring: (i) occasionally binding collateral constraints in the financial sector with significant cross-border exposure; and (ii) global supply chains, allowing us to match the asymmetry of spillovers across contractionary versus expansionary monetary policy shocks. We find clear asymmetries in the transmission of US monetary policy, with significantly larger spillovers during contractionary episodes under both conventional and unconventional monetary policy changes. Our results also reveal that the greater the size of international credit and supply chain networks and the policymakers' aversion to exchange rate fluctuations in the rest of the world, the greater the spillover effects of US monetary policy shocks.
Keywords: E52; F41; E44; 330; supply chains; capital flows; spillovers; monetary policy; emerging markets